Role of funders in embedding tests in conservation practice - Rebecca K. Smith; Nancy Ockendon; Nida Al‐Fulaij; Alessandro Badalotti; Rachel Beattie; James Byrne; Sophia Cooke; Tiago de Zoeten; Winifred F. Frick; Stephan M. Funk; Douglas Gibbs; Lauren Gupta; et al. (Conservation Biology, 2026)
Effective conservation practice requires decisions based on reliable and relevant evidence, but significant gaps in the evidence base exist. Incorporating well‐designed tests of the effectiveness of interventions for biodiversity in conservation projects is one of the best ways to scale up the rate of evidence generation. Funders of conservation projects are uniquely positioned to support and incentivize such tests as part of the grant‐making process. Using a structured process, as 25 conservation funders and members of Conservation Evidence, we identified means of improving the effectiveness of the work funded through the support of enhanced evidence generation. We identified 11 approaches through which funders can support embedding testing, ranging from encouraging inclusion of a test in the project proposal, to designating separate funds for incorporating a test, to supporting an external testing unit to provide training and advice. The appropriate approaches vary depending on the scale, process, and type of funding. Barriers to supporting testing and potential solutions were discussed, barriers such as a lack of skills to check tests are appropriate and well designed and the additional time needed to develop, implement, and see outcomes of tests and differing types of projects. By encouraging testing of actions as part of conservation practice (where appropriate), funders will ultimately facilitate a stronger evidence base for more effective decision‐making and better outcomes for nature and society.

Assessing threats and conservation action using population viability analysis for the Critically Endangered Grenada Dove Leptotila wellsi - Catherine Peters; Anna Muir; Charlotte Hosie; Howard Nelson; Matthew Geary (Journal for Nature Conservation, 2026)

A provably stable numerical method for the anisotropic diffusion equation in confined magnetic fields - Dean Muir; Kenneth Duru; Matthew Hole; Stuart Hudson (Computer Physics Communications, 2025)

Challenges in assessing the effects of environmental governance systems on conservation outcomes - Raphael A. Ayambire; Trina Rytwinski; Jessica J. Taylor; Matthew W. Luizza; Matthew J. Muir; Cynthia Cadet; Derek Armitage; Nathan J. Bennett; Jeremy Brooks; Samantha H. Cheng; Jenny Martinez; Meenakshi Nagendran; et al. (Conservation Biology, 2025)
Effective governance is crucial for the success of conservation projects aimed at protecting wildlife populations and supporting human well‐being. However, few large‐scale, comprehensive syntheses have been conducted on the effects of different environmental governance types on conservation outcomes (i.e., biological and ecological effectiveness or effects of conservation on human well‐being), and clarity on the quantity and quality of evidence remains dispersed and ambiguous. We attempted a systematic map of the evidence on the effectiveness of different governance types to meet desired conservation outcomes in Africa, Asia, and Latin America. However, early in this effort, we observed a general lack of empirical research on the links between governance and conservation outcomes. To fill observed data gaps in the evidence base, we tried triangulating governance data from alternative sources (Protected Planet database) and pooling evidence from research conducted within the same conservation areas. Limited data were contained in the Protected Planet database, and governance types in conservation areas and landscapes were complex, making it difficult to use these approaches to assign governance types to conservation areas. To illustrate our observations from the failed systematic map attempt, we prepared a rapid evidence map that outlines a subset of the evidence base of articles linking governance types and governance principles with conservation outcomes. Only 3.2% (34 of 1067) of the articles we screened directly related conservation outcomes to governance type, and even fewer related governance principles to conservation outcomes. Based on our findings, we recommend improving the evidence base by supporting empirical research and increasing the availability and quality of governance data in freely accessible databases. These recommendations are critical for enhancing understanding of the role of governance in conservation projects and improving conservation outcomes.

Funding evidence‐based conservation - Danni Parks; Nida Al‐Fulaij; Clare Brook; Stuart H. M. Butchart; Jean‐Gaël Collomb; David Cope; Simon Dowell; Becky Falkingham; Winifred F. Frick; Douglas Gibbs; Emily E. Gray; Nicolas Heard; et al. (Conservation Biology, 2022)

New haplotypes found in stranded long‐finned pilot whales ( Globicephala melas ) in the eastern North Atlantic and adjacent waters - Rachel J. Ball; Ashleigh Kitchiner; Nicholas J. Davison; Andrew Brownlow; Simon Berrow; Niall J. McKeown; Lonneke L. IJsseldijk; Matthew Geary; Ian McDowall; Anna P. Muir (Marine Mammal Science, 2022)
Long‐finned pilot whale ( Globicephala melas ) mitochondrial (mtDNA) genetic diversity is considered low, especially in the North Atlantic, where only seven haplotypes have been recorded in previous studies using a 345 bp control region fragment. Such studies have not included samples from Ireland or the Netherlands. In this study we analyzed a longer sequence of the mtDNA control region (631 bp) from individuals stranded around Ireland, Scotland, and the Netherlands between 1995 and 2019 ( n = 180). Nine haplotypes were identified, of which five were newly described (haplotype diversity h = 0.511). Pairwise tests revealed significant differentiation between the Irish and Scottish samples. Potential confounding factors are discussed but given that failure to recognize population structure may compromise conservation efforts, the findings show the need for further investigation using nuclear markers. Six mass stranding events were included, of which one event reported two haplotypes among individuals confirming a mixing of matrilineal groups. Although the permanence of this combination cannot be determined, this is the first record of such an occurrence within the North Atlantic. This study shows that stranding sample databases are a useful resource for genetic studies and provides new insights into genetic diversity of long‐finned pilot whales in the eastern North Atlantic and adjacent waters.

Loss of vacuolar acidity results in iron-sulfur cluster defects and divergent homeostatic responses during aging in Saccharomyces cerevisiae - Kenneth L. Chen; Toby N. Ven; Matthew M. Crane; Matthew L. C. Brunner; Adrian K. Pun; Kathleen L. Helget; Katherine Brower; Dexter E. Chen; Ha Doan; Justin D. Dillard-Telm; Ellen Huynh; Yen-Chi Feng; et al. (GeroScience, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Academic Research Training for a Nonacademic Workplace: a Case Study of Graduate Student Alumni Who Work in Conservation - MATTHEW J. MUIR; MARK W. SCHWARTZ (Conservation Biology, 2009)
Graduate education in conservation biology has been assailed as ineffective and inadequate to train the professionals needed to solve conservation problems. To identify how graduate education might better fit the needs of the conservation workplace, we surveyed practitioners and academics about the importance of particular skills on the job and the perceived importance of teaching those same skills in graduate school. All survey participants ( n = 189) were alumni from the University of California Davis Graduate Group in Ecology and received thesis‐based degrees from 1973 to 2008. Academic and practitioner respondents clearly differed in workplace skills, although there was considerably more agreement in training recommendations. On the basis of participant responses, skill sets particularly at risk of underemphasis in graduate programs are decision making and implementation of policy, whereas research skills may be overemphasized. Practitioners in different job positions, however, require a variety of skill sets, and we suggest that ever‐increasing calls to broaden training to fit this multitude of jobs will lead to a trade‐off in the teaching of other skills. Some skills, such as program management, may be best developed in on‐the‐job training or collaborative projects. We argue that the problem of graduate education in conservation will not be solved by restructuring academia alone. Conservation employers need to communicate their specific needs to educators, universities need to be more flexible with their opportunities, and students need to be better consumers of the skills offered by universities and other institutions.

Revisiting the Links between Governance and Biodiversity Loss - Robert J. Smith; Robert D. J. Muir; Matthew J. Walpole; Andrew Balmford; Nigel Leader‐Williams (Conservation Biology, 2007)